2007
DOI: 10.1080/09585190601068243
|View full text |Cite
|
Sign up to set email alerts
|

Cultural orientations and preferences for HRM policies and practices: the case of Oman

Abstract: This study empirically examines the influence of cultural orientations on employee preferences of human resource management (HRM) policies and practices in Oman. Data were collected from 712 employees working in six large Omani organisations. The findings indicate that there are a number of differences among Omani employees regarding value orientations due especially to age, education and work experience. The findings show a strong orientation towards mastery, harmony, thinking and doing, and a weak orientatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
56
2
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(67 citation statements)
references
References 37 publications
6
56
2
1
Order By: Relevance
“…The country has transformed from a harshly ruled, isolationist Sultanate into an economically liberalized monarchy seeking to integrate the country into the global economy (Aycan et al, 2007). In 2008, the total population was 2.867 million made up of 1.967 million Omanis and 900,000 expatriate workers.…”
Section: Omanmentioning
confidence: 99%
“…The country has transformed from a harshly ruled, isolationist Sultanate into an economically liberalized monarchy seeking to integrate the country into the global economy (Aycan et al, 2007). In 2008, the total population was 2.867 million made up of 1.967 million Omanis and 900,000 expatriate workers.…”
Section: Omanmentioning
confidence: 99%
“…The advocates of the convergence approach argue that management is management, and that it is associated with a set of principles and techniques which can be implemented universally (see Al-Kazemi and Ali 2002;Harris et al 2003;Schneider and Barsoux 2003;Pugh and Hickson 2004). Nevertheless, it has been observed that management models and practices do vary considerably from country to country (Easterby-Smith et al 1995;Allinson and Hayes 2000;Aycan et al 2007). The infl uential research by Hofstede (1991) demonstrates that management theories often refl ect the socio-cultural characteristics of their settings.…”
Section: Introductionmentioning
confidence: 99%
“…Other themes emerging from the literature include the effects of regulations on HRM in the Saudi Arabia private sector (Mellahi, 2007) and on employment policy in Kuwait (AlEnizi, 2002), the impact of HRM on organisational commitment in the banking sector in Kuwait (Zaitouni et al, 2011), the efficacy of high-performance work practices in Algerian firms (Ramdani et al, 2014), the impact of HRM practices and corporate entrepreneurship on firm performance in Turkish firms (Kaya, 2006), talent management strategies in the UAE (Singh and Sharma, 2015), the impact of cultural value orientations on preferences for HRM (Aycan et al, 2007), HRM and labour productivity in Libyan oil companies (Mohamed et al, 2015), HRM and innovation in the Iranian electronics industry (Manafi and Subramaniam, 2015) and career development in Oman (Khan et al, 2015).…”
Section: Developments In Middle East Hrmmentioning
confidence: 99%